Acceptable experimentation?: Investigating reasons for same-sex infidelity and women's anticipated responses to a male partner's hypothetical same-sex infidelity. (1st July 2020) - Denes, Amanda; Dillow, Megan R.; Lannutti, Pamela J.; Bevan, Jennifer L.
Abstract: The present investigation explored how individuals in heterosexual relationships process and respond to a romantic partner's imagined infidelity with someone of the same sex. Study 1 entailed a qualitative analysis of individuals' reported reasons for their own or a friend's same-sex infidelity, revealing that individuals engage in same-sex infidelity for unique motives, such as for experimentation. Study 2 focused specifically on female participants and tested whether the motivation for infidelity (e.g., vengeance, experimentation, jealousy) predicted differences in participants' expectations of how they would respond to the infidelity. The findings revealed that women were the most likely to report that they would confront the situation, continue the relationship, and show benevolence when experimentation was the underlying reason for the infidelity. These findings and their implications for understanding women's reactions to their male partners' same-sex infidelity are discussed.